PENGARUH PENDIDIKAN AKIDAH AKHLAK TERHADAP PERILAKU SOSIAL - Imas Kurniasih; Rifqi Rohmatulloh; Ibnu Imam Al Ayyubi (Al-Mau'izhoh, 2022)
At the madrasah level, the subject of aqidah morals includes the values of aqidah and morals. Behavior can be said to be correlative with educational goals. Education of character and morals is the soul and goal of Islamic education, the main goal of Islamic religious education is synonymous with the life goals of every Muslim. This study seeks to determine the influence between Aqidah Akhlak Education and students' social behavior. Data collection was carried out through observation, interviews, questionnaires, and literature, using explanatory methods, qualitative and quantitative data analysis which were processed statistically with product moment as well as percentage results. The results showed that the indicators of aqeedah and moral education with social behavior as a percentage showed positive results, then with the t test it was found that there was a significant influence between aqidah moral education and social behavior. This can be due to the exemplary and guidance given to students to have good morals, of course this is obtained from educators, parents and a good environment. So, it can be stated that the Aqidah Akhlak Education that is applied influences more or less the social behavior of students in living their daily lives.Keywords: Faith, Morals, and Social Behavior